Analysis of Orthopaedic Research Produced During the Wars in Iraq and Afghanistan. Issue 9 (September 2015) - Balazs, George C.; Dickens, Jonathan F.; Brelin, Alaina M.; Wolfe, Jared A.; Rue, John‐Paul H.; Potter, Benjamin K.
Abstract: Background: Military orthopaedic surgeons have published a substantial amount of original research based on our care of combat‐wounded service members and related studies during the wars in Iraq and Afghanistan. However, to our knowledge, the influence of this body of work has not been evaluated bibliometrically, and doing so is important to determine the modern impact of combat casualty research in the wider medical community. Questions/purposes: We sought to identify the 20 most commonly cited works from military surgeons published during the Iraq and Afghanistan conflicts and analyze them to answer the following questions: (1) What were the subject areas of these 20 articles and what was the 2013 Impact Factor of each journal that published them? (2) How many citations did they receive and what were the characteristics of the journals that cited them? (3) Do the citation analysis results obtained from Google Scholar mirror the results obtained from Thompson‐Reuters' Web of Science? Methods: We searched the Web of Science Citation Index Expanded for relevant original research performed by US military orthopaedic surgeons related to Operation Iraqi Freedom and Operation Enduring Freedom between 2001 and 2014. Articles citing these studies were reviewed using both Web of Science and Google Scholar data. The 20 most cited articles meeting inclusion criteria were identified and analyzed by content domain, frequency of citation, and sources in which they were cited. Results: Nine of these studies examined the epidemiology and outcome of combat injury. Six studies dealt with wound management, wound dehiscence, and formation of heterotopic ossification. Five studies examined infectious complications of combat trauma. The median number of citations garnered by these 20 articles was 41 (range, 28‐264) in Web of Science. Other research citing these studies has appeared in 279 different journals, covering 26 different medical and surgical subspecialties, from authors in 31 different countries. Google Scholar contained 97% of the Web of Science citations, but also had 31 duplicate entries and 29 citations with defective links. Conclusions: Modern combat casualty research by military orthopaedic surgeons is widely cited by researchers in a diverse range of subspecialties and geographic locales. This suggests that the military continues to be a source of innovation that is broadly applicable to civilian medical and surgical practice and should encourage expansion of military‐civilian collaboration to maximize the utility of the knowledge gained in the treatment of war trauma. Level of Evidence: Level IV, therapeutic study.